2018
DOI: 10.1002/1878-0261.12161
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals that loss of lunatic fringe (LFNG) promotes melanoma metastasis

Abstract: Metastasis is the leading cause of death in patients with advanced melanoma, yet the somatic alterations that aid tumour cell dissemination and colonisation are poorly understood. Here, we deploy comparative genomics to identify and validate clinically relevant drivers of melanoma metastasis. To do this, we identified a set of 976 genes whose expression level was associated with a poor outcome in patients from two large melanoma cohorts. Next, we characterised the genomes and transcriptomes of mouse melanoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…By contrast, loss of Lfng which suppresses JAG1-induced NOTCH1 signalling in mammary epithelium, in cooperation with MET/CAVEOLIN gene amplification, promotes basal-like breast cancer [109]. LFNG also functions as a tumor suppressor in melanoma metastasis [110], and in mouse models of pancreatic [111] and prostate cancer [112]. These results reveal fundamental roles of Fringe in regulating Notch signalling.…”
Section: O-fucose Glycansmentioning
confidence: 99%
“…By contrast, loss of Lfng which suppresses JAG1-induced NOTCH1 signalling in mammary epithelium, in cooperation with MET/CAVEOLIN gene amplification, promotes basal-like breast cancer [109]. LFNG also functions as a tumor suppressor in melanoma metastasis [110], and in mouse models of pancreatic [111] and prostate cancer [112]. These results reveal fundamental roles of Fringe in regulating Notch signalling.…”
Section: O-fucose Glycansmentioning
confidence: 99%
“…The results indicated that the chemokine CCL5 and CXCL11 expression was significantly decreased in CDKN2A-deleted melanoma cell lines ( Figure 3A ). B16F0 cells were described as CDKN2A null cell line ( 36 ). The CDKN2A expression was restored in B16F0 cells by transfection with the lentivirus containing proximal promoter-drived p16INK4 (the protein product of CDKN2A) expression.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes are related to apoptosis ( Casp7 ) and mitotic arrest ( Fbl2 ) [ 43 ]. In addition, Lfng (Lunatic fringe) encodes a glycosyltransferase that inhibits metastasis in melanoma cells [ 44 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%